"Our organs have a purpose": body image acceptance in Latina breast cancer survivors. Issue 11 (26th September 2016) - Buki, Lydia P.; Reich, Micaela; Lehardy, Emaan N.
Abstract: Objective: Studies examining body image concerns among breast cancer survivors have primarily captured the experiences of non‐Latina white women. Thus, little is known about body image concerns among Latinas. To address this gap, we examined Latina breast cancer survivors' lived experiences related to body image. Methods: Twenty‐seven Latina breast cancer survivors provided data through focus groups and individual interviews as part of a larger study conducted by the first author. In the current paper, we conducted a secondary thematic analysis to uncover women's experiences unique to body image concerns. Results: We identified 2 themes related to women's experiences with body image: (a) perceptions of loss and reconstruction and (b) process of achieving body image acceptance. The salience of these themes varied as a function of survivorship stage and type of surgery. Conclusions: Body image concerns are distressing for Latina breast cancer survivors. Accepting their altered appearance was an ongoing and complex process. Clinical implications include the need for psychoeducational programs and tailored interventions to enhance women's body image acceptance.